2017
DOI: 10.4187/respcare.05127
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Delivery Through Adult High Flow Nasal Cannula With Heliox and Oxygen

Abstract: With a distressed breathing pattern, aerosol delivery was greater at 30 and 50 L/min than with a quiet breathing pattern. Trends toward higher inhaled dose with heliox during HFNC were not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 15 publications
9
57
2
Order By: Relevance
“…Everard et al found approximately 50% reduction in lung deposition with nasal inhalation, which is consistent with the findings of this study. Aerosol drug delivery through HFNC has gained popularity over the years and the performance of HFNC on aerosol delivery has been investigated in previous research . Similar to previous evidence, we also found that decreasing flow rate with HFNC and LFNC increases aerosol drug delivery in infants and pediatrics because of a reduction in turbulent and transitional flow.…”
Section: Discussionsupporting
confidence: 88%
“…Everard et al found approximately 50% reduction in lung deposition with nasal inhalation, which is consistent with the findings of this study. Aerosol drug delivery through HFNC has gained popularity over the years and the performance of HFNC on aerosol delivery has been investigated in previous research . Similar to previous evidence, we also found that decreasing flow rate with HFNC and LFNC increases aerosol drug delivery in infants and pediatrics because of a reduction in turbulent and transitional flow.…”
Section: Discussionsupporting
confidence: 88%
“…During simulated paediatric breathing, 1.2, 0.1 and 0% were found for gas-flow rates of 3, 10 and 20 L/min, as compared to this study's findings of 3.23 ± 1.58, 0.42 ± 0.06 and 1.17 ± 0.28% for flow rates of 2, 10 and 20 L/min. Dailey et al [36] examined the inhaled dose using a high-flow nasal cannula and reported considerably higher values of 26.7% to 27.4% at 10 L/min, 11.6% to 14.2% at 30 L/min and 3.5% to 5.9% at 50 L/min. Perry et al [13] used a lower tidal volume for the paediatric breathing profiles setting than the present study; while Dailey et al used an inspiratory-expiratory ratio of 1:2, an Albuterol sulphate mixture (2.5 mg/0.5 mL).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the majority of the loss mechanisms occurred prior to exiting the patient interface. Dailey et al [36] reported that increased flow rate could increase turbulence and impactive loss of aerosol within the tubing, which means less aerosol is reaching the patient interface and available for inhalation and/or to be released as fugitive aerosol.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Reminiac et al reported that the respirable mass of drug was significantly higher during simulated respiratory distress than simulated quiet breathing [22]. Dailey et al showed that with a distressed breathing pattern, aerosol delivery was greater at 30 and 50 LPM than with a quiet breathing pattern [33].…”
Section: Discussionmentioning
confidence: 99%